2015
DOI: 10.4317/jced.51828
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of transcutaneous electrical nerve stimulation (TENS) on whole salivary flow rate

Abstract: Background: Saliva plays a critical role in maintaining oral homeostasis; it modulates the ecosystem through lubrication of the alimentary bolus, protection against microorganisms, buffer and repair of the oral mucosa, and helps in dental re-mineralization. Various local and systemic factors such as medications, radiation therapy, systemic conditions, etc. can lead to reduction in salivary flow. A decrease in salivary function, known as Xerostomia, increases a patient’s risk for caries and other oral infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Therefore, the present study was designed to test shortterm daily facial muscle training for 6 months. An earlier study has reported that sonic toothbrushes stimulate salivary flow in a xerostomic population (17). The results of this study are also consistent; however, the precise mechanism remains unclear.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the present study was designed to test shortterm daily facial muscle training for 6 months. An earlier study has reported that sonic toothbrushes stimulate salivary flow in a xerostomic population (17). The results of this study are also consistent; however, the precise mechanism remains unclear.…”
Section: Discussionsupporting
confidence: 88%
“…Transcutaneous electrical nerve stimulation, in which salivation is induced by electrodes placed on skin, has recently been shown to be effective on whole saliva (17). This suggests that salivary flow can be enhanced by the stimulation of adjacent oral structures.…”
Section: Introductionmentioning
confidence: 99%
“…Longman et al (27) found an increase in salivary flow by 71% (pre-test = 0.07 ± 0.03 mL/min; post-test = 0.12 ± 0.03 mL/min) after a single application of electrical stimulation. Similarly, Aggarwal et al (28) found, in apparently healthy individuals, an increase in salivary flow in the order of 13% (0.16 mL/min/ Pre-test = 1.25 mL/min; post-test = 1.41 mL/min), after a single application of TENS (100Hz frequency, 100 to 150uS pulse width, and electrodes allocated in the region over the parotid glands). In another study, which included a heterogeneous sample composed of patients with the most various pathologies (e.g., diabetics; users of antidepressants, antipsychotics and diuretics; and post-menopausal women), 5-minute electrical stimulation with the same parameters used in the present study (50Hz and 250uS) also resulted in benefits (pre-test: 2.343 mL/min; post-test: 3.053) (29) .…”
Section: Discussionmentioning
confidence: 71%
“…These results suggested that the increase in saliva flow may be promoted by stronger stimulation during NMES. In a previous study, Hersheal et al ( 26 ) reported that saliva flow quantity increased following transcutaneous electrical nerve stimulation (TENS) with low frequency applied to the parotid gland in healthy adults. As a similar type of stimulation was applied in that study, their results were similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty healthy adult volunteers (nine males, mean age ± SD = 27.9 ± 3.8 years) participated in this study as subjects. Exclusion criteria were those with salivary gland disease, those who took medications which influenced salivation, and smokers ( 19 ). Written informed consent was obtained from each participant.…”
Section: Methodsmentioning
confidence: 99%